Treatment patterns, persistence with therapy, and outcomes of ustekinumab in Crohn's disease: Real‐world data analysis. Issue 2 (26th January 2022) - Banon, Tamar; Weil, Clara; Borsi, Andras; Chodick, Gabriel; Shakked, Zehavi; Barit Ben‐David, Nava
Abstract: Background and Aim: In 2017, ustekinumab (UST) was included in Israel's National Basket of Health Services for treatment of biologic‐experienced Crohn's disease (CD) patients with moderately to severely active disease. This study aims to provide real‐world evidence on persistence and clinical outcomes among early users of UST. Methods: This retrospective cohort study was conducted using data from Maccabi Healthcare Services (MHS; 2.5‐million‐member state‐mandated health provider, Israel). Adult patients with a CD diagnosis code who had ≥1 dispensed UST prescription in 2017–2018 and at least 12 months of prior continuous health plan enrollment were included. Outcomes, including treatment discontinuation, dose‐escalation (based on shortened intervals between purchases), CD‐related surgery, CD‐related hospitalization, corticosteroid (CS) discontinuation, and use of opioids were evaluated from the date of first dispensed UST through the end of 2019 using Kaplan–Meier analysis. Results: A total of 162 eligible patients (81 [49.4%] female; median age 34.4 years [IQR 23.2–46.3]; median years since CD diagnosis 8.6 [IQR 4·8–16.0]) were enrolled in the study. Discontinuation rate after 365 and 540 days of follow‐up was 27.8% and 35.6%. Dose escalation was estimated at 15.4% and 28.6%, respectively. The first‐year cumulative rate of CD‐related surgery and CD‐related hospitalization were estimated at 4.7% and 9.8%, respectively. Conclusion: In this real‐world CD cohort of UST users, results suggest persistence is relatively high as compared to other biologics for CD. Comparative effectiveness of different biologic treatments for CD in this population should be further explored. Abstract : This retrospective research follows a real‐world cohort of UST initiators for the treatment of CD with up to 2 years of follow‐up. This study explored therapy persistence, dose increase, and time‐to‐IBD‐related procedures following the initiation date.